Flexural Behavior of Blended Slurry-Infiltrated Fibrous Concrete Boards Made with Hybrid fibers and Nano Slag - Adnan Kadhim Jawad; Isam Mohamad Ali; Mohammed Kareem Abed; Ikram Ameen Saeed; Mohammed Salah Nasr; Tameem Mohammed Hashim (International Journal of Computational and Experimental Science and Engineering, 2025)
High volume fraction of fibers with notable improvements in strength, durability, ductility, and toughness are the main fundamental advantages of slurry infiltrated fibrous concrete (SIFCON). The experimental study presented in this work examines the flexural behavior of composite boards made of SIFCON. It also looks into the effect of hybrid fiber reinforcement on toughness and strength characteristics, as well as the addition of binary and ternary blends of SIFCON under flexural loading. Thirty boards measuring an effective span of 300 mm, width of 150 mm and 25 mm thickness were cast and tested at 28 days in order to examine the toughness, flexural strength, load-deformation and microstructural analysis characteristics. Various volume fractions of steel and plastic fibers of (8+0, 7+1, 6+2, 5+3, and 4+4%) respectively were used. After that, the specimens were divided into two groups: binary (cement+ micro silica) and ternary (cement+ micro silica+ nano slag). Also, a SEM test was used to track microstructural features of fractured surfaces. The results showed that adding nanomaterials clearly enhanced the microstructure's density and decreased the number of pores in the SIFCON boards that were created. Moreover, the steel fiber demonstrated a 40% increase in flexural strength compared to the hybrid fiber system composed of 4% steel fiber and 4% plastic fiber in the binary blend. In the ternary blend, this difference was reduced to 34%. Additionally, the incorporation of nano slag enhanced the strength properties of the produced SIFCON mixes by up to 22% in the ternary blends.